Order and innovation in the Middle Ages : essays in honor of Joseph R. Strayer - Jordan, William Chester, 1948-; McNab, Bruce, 1945-; Ruiz, Teofilo F., 1943- (Princeton legacy library., 1976)
The Middle Ages were for many years generally viewed as a period when faith and order supported a rigid society. By painstaking archival research, historians such as Joseph R. Strayer and the contributors to this volume have gradually replaced this view with a regard for the period as a time of great intellectual diversity.These essays, divided into five groups, probe the themes of order and innovation as they appear in medieval government; finance; trade and urban life; social arrangements; and aspects of the personality and goals of the individual. The contributors focus on England, France, and the Mediterranean from about the eleventh to about the sixteenth century.Contributors: Frederic Kreisler, Charles Radding, Giles Constable, William Bowsky, John Freed, Phillippe Wolff, Thomas Bisson, Richard Kaeuper, John Benton, Archibald Lewis, William Jordan, Rhiman Rotz, Robert Baker, Robert Lopez, Teofilo Ruiz, Raphael DeSoignie, Bennett Hill, Frederic Cheyette, Jan Rogozinski, Bruce McNab, Lester Little, Robert Lerner, Elizabeth Brown, Charles Wood, and Gaines Post.Originally published in 1976.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.